Very Urgent Carotid Endarterectomy Does Not Increase the Procedural Risk. Issue 2 (February 2015) - Rantner, B.; Schmidauer, C.; Knoflach, M.; Fraedrich, G.
<x xml:space="preserve">Abstract</x> Objectives The timing of CEA for symptomatic internal carotid artery (ICA) stenosis remains a matter of controversy. Recent registry data showed a significantly increased risk, especially in the very early days after the onset of symptoms. In this study the outcome of CEA in the hyperacute phase has been investigated. Methods The outcome of CEA for symptomatic ICA stenosis between January 2004 and December 2013 has been retrospectively analyzed. Patients were divided into four timing groups: surgery within 0 and 2 days, between 3 and 7 days, 8 and 14 days, and thereafter. The post-operative 30 day stroke and death rates were assessed. Results A total of 761 symptomatic patients (40.1% with transient ischemic attack [TIA], 21.3% with amaurosis fugax, and 38.6% with ischemic stroke) were included, with an overall peri-operative stroke and death rate of 3.3%. A stroke and death rate of 4.4% (9/206) for surgery within 0 and 2 days, 1.8% (4/219) between 3 and 7 days, 4.4% (6/136) between 8 and 14 days, and 2.5% (5/200) in the period thereafter (p = .25 for the difference between the groups) was observed. The timing of surgery did not influence the peri-operative outcome in a multivariate regression analysis (OR 0.93 [0.63–1.36], p = .71). Conclusions These data show that very urgent surgery in symptomatic patients can be performed without increased procedural risk. Given the fact that ruptured plaques with neurological symptoms carry the highest risk of a recurrent ischemic event in the first 2 days, treating patients as soon as possible to offer the highest benefit in stroke prevention is recommended.